Identification of short cycle, heat-tolerant potato (Solanum tuberosum) clones for the semi-arid agro-ecology - Kadian, M S; Luthra, S K; Patel, N H; Bonierbale, M; Singh, S V; Sharma, Neeraj; Kumar, V; Gopal, Jai; Singh, B P (The Indian Journal of Agricultural Sciences, 2012)
Advanced potato (Solanum tuberosum L.) clones developed by the International Potato Center (CIP), Lima and locally grown varieties were evaluated for agronomic performance in winter season under short-day conditions at the Agricultural Research Station (ARS), Ladol, Gujarat during the 2009–11. Ladol, selected for screening of the clones has higher mean night and day temperatures during potato crop seasons compared to other potato growing areas in India. Out of nine advanced clones CIP 301029.18, CIP 388972.22 and CIP 393708.31 had significantly higher yield of marketable tuber at the tune of 52.6, 49.3 and 52.6 tonnes/ ha, respectively, along with desirable tuber shape, size, colour and more than 20% dry matter. Whereas, CIP 388972.22 was found suitable for processing as fried chips based on its hunter colour quality.